Thrombotic adverse events associated with TNF-alpha blockers: a real-world pharmacovigilance analysis of the FAERS database - Lijuan Song; Nan Yang; Xinglong Xing; Yicong Zhao; Jingkai Di (Frontiers in Pharmacology)
ObjectiveThis research is designed to explore the connection between tumor necrosis factor-α (TNF-α) blocker drugs and thrombotic adverse events.MethodsThe study included data from the FDA Adverse Event Reporting System (FAERS) spanning from the first quarter of 2004 to the first quarter of 2024. We employed the disproportional analysis approach to analyze the signals of thrombosis-related adverse events associated with TNF-α blockers. Moreover, subgroup analyses were conducted to investigate the circumstances of different age and gender groups. Additionally, the induction time and Weibull distribution were utilized for the further interpretation of the data.ResultsDuring the study period, among 1,382,627 patients in the FAERS database who had adverse events linked to TNF-α inhibitors, 9,714 could be attributed to thrombosis-related adverse events. In the remaining patients, different types of infection events accounted for a large proportion of the proportion. (N = 165,765) Thrombosis-related adverse event signals were detected in all five types of TNF-α inhibitor drugs. Among them, in the analysis of adalimumab, the adverse event signal of postpartum thrombosis was the strongest, and the positive signal of axillary vein thrombosis was the weakest. The analysis based on gender subgroups discovered some positive signals of adverse events that were not observed in the overall population. The Weibull distribution analysis indicated that all five drugs exhibited an premature aging type characteristic, and their induction decreased gradually over time.ConclusionThis study suggests that TNF - α blockers are associated with various adverse events of thrombosis, with different risks in different patient groups and treatment stages. Clinical doctors should assess individual thrombosis risk and closely monitor coagulation related indicators when using TNF - α inhibitors. This study offers valuable insights for optimizing treatment and improving safety.